Activity‐Selectivity Trends in Electrochemical Urea Synthesis: Co‐Reduction of CO2 and Nitrates Over Single‐Site Catalysts - Qinglan Zhao; Yushen Liu; Yuan Zhang; Shangqian Zhu; Hongming Xu; Mohammad Farhadpour; Fei Xiao; Minghui Xing; Dapeng Cao; Xueping Qin; Tejs Vegge; Minhua Shao (Advanced Science, 2025)
Abstract Electrochemical co‐reduction of carbon dioxide and nitrates (CO2NO3RR) holds promise for sustainable urea production. However, the sluggish kinetics of the sixteen‐electron transfer and unclear mechanistic understanding strongly impede its development. Here, combined experimental and computational approaches are employed to screen a series of metal phthalocyanine as model catalysts (MPcs, M = Zn, Co, Ni, Cu, and Fe) to uncover the activity‐selectivity trends in electrochemical CO2NO3RR. The theoretical simulations reveal that the thermodynamics of urea synthesis is significantly influenced by key intermediates, where the enhanced adsorption of *HOOCNO, coupled with reduced adsorptions of *N and *COOH, and moderate adsorption of *H2O, can significantly promote the urea production. ΔG*HOOCNO−ΔG*N−ΔG*COOH+ΔG*H2O as a potential descriptor is proposed for predicting the efficiency of CO2NO3RR toward urea formation. The findings provide systematic guidance for the future design of high‐efficiency catalysts for urea electrosynthesis, addressing a crucial need for sustainable nitrogen fixation.